The Person with a Learning Disability as a Minority Group Member - Coughlin, Dan (Journal of learning disabilities, 1997)
Last semester, while concluding an autobiography for a class assignment, the author came to the realization that being a person with a learning disability constitutes a strong connection to people of other minority groups. This article will develop that theme, searching relevant issues through applied sociological principles and utilizing personal commentaries by members of those groups.